2004
DOI: 10.1073/pnas.0406844101
|View full text |Cite
|
Sign up to set email alerts
|

Integration of reproductive meristem fates by a SEPALLATA -like MADS-box gene

Abstract: Reproductive transition, inflorescence architecture, meristem patterning, and floral organ identity have been studied as distinct research areas in plant science. By using the ornamental plant Gerbera, we demonstrate that all of these keystone aspects of reproductive meristematic fate are integrated genetically by a single SEPALLATA-like MADS-box gene from a functional class designated previously as ''floral homeotic'' or ''organ identity.'' This extended regulatory network has not been elaborated in the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 40 publications
6
119
0
2
Order By: Relevance
“…Indeed, flowers from plants mutant simultaneously for three SEP genes still display a normal AG expression pattern, but entirely lack FM termination (Pelaz et al, 2000;Ditta et al, 2004). A similar commitment of class E proteins in FM termination was described in several other species, including petunia, gerbera (Gerbera hybrida), and tomato (Solanum lycopersicum; Angenent et al, 1994;Pnueli et al, 1994;Vandenbussche et al, 2003;Uimari et al, 2004). It is worth noting that in both petunia and rice, ovule identity (also called class D) genes also appear to promote FM termination (Ferrario et al, 2006;Dreni et al, 2007).…”
Section: Fm Termination Relies On a Complex Multilevel Activation Of Agmentioning
confidence: 56%
“…Indeed, flowers from plants mutant simultaneously for three SEP genes still display a normal AG expression pattern, but entirely lack FM termination (Pelaz et al, 2000;Ditta et al, 2004). A similar commitment of class E proteins in FM termination was described in several other species, including petunia, gerbera (Gerbera hybrida), and tomato (Solanum lycopersicum; Angenent et al, 1994;Pnueli et al, 1994;Vandenbussche et al, 2003;Uimari et al, 2004). It is worth noting that in both petunia and rice, ovule identity (also called class D) genes also appear to promote FM termination (Ferrario et al, 2006;Dreni et al, 2007).…”
Section: Fm Termination Relies On a Complex Multilevel Activation Of Agmentioning
confidence: 56%
“…Many novel functions for these regulators have been detected using transgenic plants that show distinct phenotypes. The results emphasize the importance of using gerbera for comparative studies with other model species such as Arabidopsis thaliana (Yu et al 1999, Kotilainen et al 2000, Uimari et al 2004, Teeri et al 2006c. Recent studies have employed expressed sequence tag (EST) sequencing and cDNA microarrays for identification of new gene family members related to both secondary metabolism and flower development (Laitinen et al 2005).…”
Section: Biotechnology In Horticultural Speciesmentioning
confidence: 94%
“…39, with the following exceptions: probe concentration was 0.7 g/ml/kb and detection time was 40 -45 h. SEM analysis of the Gerbera flower primordia was performed as described in ref. 5.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that many MADS box genes encoding known regulators of flower organ development are expressed gradientially along the capitulum radius. While this may suggest that different MADS protein complexes participate in developmental regulation of individual flower types, transgenic experiments show that such complexes are not independently sufficient (4,5). Indeed, classical genetics has shown that the presence or absence of ray flowers in Asteraceae capitula appears to be under control of one or two major and several modifier genes (reviewed in ref.…”
mentioning
confidence: 99%